A pilot feasibility randomised controlled trial of two behaviour change interventions compared to usual care to reduce substance misuse in looked after children and care leavers aged 12-20 years: The SOLID study. - Hayley Alderson; Eileen Kaner; Elaine McColl; Denise Howel; Tony Fouweather; Ruth McGovern; Alex Copello; Heather Brown; Paul McArdle; Deborah Smart; Rebecca Brown; Raghu Lingam (PLoS ONE, 2020)
Background Young people in state care, often due to abuse or neglect, have a four-fold increased risk of drug and alcohol use compared to their peers. Aim The SOLID study aimed to investigate the feasibility of a definitive randomised controlled trial, comparing two behaviour change interventions to reduce risky substance use (illicit drugs and alcohol), and improve mental health, in young people in care. Methods We recruited young people in care aged 12-20 years, self-reporting substance use within the previous 12 months and residing in 1 of 6 participating local authority sites in the North East of England. Participants were randomised to either i. Motivational Enhancement Therapy (MET), ii. Social Behaviour and Network Therapy (SBNT) or iii. Control (usual care). All interventions were delivered by trained drug and alcohol workers. Follow-up data were collected 12 months post recruitment. Feasibility for trial progression was compared to pre-specified stop: go criteria (recruitment of 60% of eligible participants, 80% of participants attending 60% of offered sessions and retention of 70% of participants at 12 month follow up). Results Of 1450 eligible participants, 860 (59%) were screened for drug and alcohol use by social workers, 211 (24.5%) met inclusion criteria for the trial and 112 young people (7.7%) consented and were randomised. Sixty of these 112 participants (54%) completed 12-month follow-up questionnaires. Only 15 out of the 76 (20%) participants allocated to an intervention arm attended any of the offered MET or SBNT sessions. Conclusion By reference to pre-specified stop: go criteria it is not feasible to conduct a definitive trial for SOLID in its current format. Despite co-designing procedures with staff and young people in care, the screening, referral and treatment pathway did not work here. Future work may require dedicated clinically embedded research resource to evaluate effectiveness of new interventions in services.